The Effect of Participatory Leadership Style and Non-Physical Work Environment on Employee Job Satisfaction at CV. Citra Nusantara Bukittinggi - Setiawan, Renaldi; Andriani , Chichi (Cakrawala Repositori IMWI, 2025)
This study aims to analyze and determine the influence of participative leadership style on employee job satisfaction, and (2) the influence of the non-physical work environment on employee job satisfaction at CV. Citra Nusantara Bukittinggi. This study was conducted on employees of CV. Citra Nusantara Bukittinggi. The type of research is quantitative descriptive research. The population in this study comprises employees of CV. Citra Nusantara Bukittinggi, with the sampling technique being total sampling, involving all employees a total of 46 individuals. The data used are both primary and secondary data. Data collection techniques include questionnaires. The data analysis methods utilize descriptive analysis, classical assumption tests, multiple linear regression, F tests, t tests, and determinant coefficients. The analysis was conducted using SPSS 22 with an alpha of 0.05. The results of the study show that participative leadership style has a significant effect on employee job satisfaction, and the non-physical work environment has a significant effect on employee job satisfaction at CV. Citra Nusantara Bukittinggi.